Development of Affective Attitude Instruments: Bibliometrics on the Scopus Database 2014 – 2023 - Suyono Suyono; Nuryani Dwi Astuti; Heri Retnawati; Syarief Fajaruddin; Ari Setiawan; Mohd Kasturi Nor Abd Aziz; Satrian Suhendar (Jurnal Pendidikan MIPA, 2026)
This study aims to map publication trends, knowledge structures, and research gaps in the development of affective attitude instruments indexed in Scopus during 2014–2023. This study uses bibliometric analysis. A literature search was conducted in the Scopus database using the keywords "Development of Attitude Instruments" OR "Attitude Instruments" OR "Affective Attitudes" OR "Students' Attitudes Towards Learning". From 1,033 initial documents, after a screening process based on inclusion criteria (period 2014–2023, open access, English language, journal/conference paper/review article type) and manual review, 689 documents were obtained and analyzed using Biblioshiny (R) for thematic mapping and VOSviewer for other analyses. The results show three main findings. First, the COVID-19 pandemic became a turning point, shifting the focus from classical attitude measurement to adaptive instruments for online learning, with a surge in publications in 2021–2022 in response to the need to measure students' anxiety, adaptation, and mental health. Second, there is a systematic geographical imbalance in which developed countries (the US, the UK, and Canada) dominate as centers of psychometric theory, while Indonesia presents strategic opportunities; demographic bias is also evident in the dominance of binary gender variables, which reduce pedagogical complexity. Third, the thematic map reveals the most pressing missing link: the disconnection between the validity and reliability themes and the e-learning system, indicating that the validation standards for attitude instruments remain oriented towards face-to-face learning and have not adapted to the era of Society 5.0. This study concludes that the development of affective attitude instruments has transformed from classical psychometrics to the digital era and commercialization. The most strategic future research agenda is to develop an attitude instrument validation framework that integrates with digital learning platforms, bridges the gap between student intentions and behavior, and simultaneously supports character education and digital transformation. Keywords: bibliometric analysis, attitudinal instrument, scopus-indexed journals (2014–2023) R and VOSViewer software.